Predictors of Epileptic Seizures and Ability to Work in Supratentorial Cavernous Angioma Located Within Eloquent Brain Areas. Issue 4 (29th March 2019) - Zanello, Marc; Goodden, John R; Colle, Henry; Wager, Michel; Hamer, Philip C De Witt; Smits, Anja; Bello, Lorenzo; Tate, Matthew; Spena, Giannantonio; Bresson, Damien; Capelle, Laurent; Robles, Santiago Gil; et al.
Abstract: BACKGROUND: The postoperative outcomes and the predictors of seizure control are poorly studied for supratentorial cavernous angiomas (CA) within or close to the eloquent brain area. OBJECTIVE: To assess the predictors of preoperative seizure control, postoperative seizure control, and postoperative ability to work, and the safety of the surgery. METHODS: Multicenter international retrospective cohort analysis of adult patients benefitting from a functional-based surgical resection with intraoperative functional brain mapping for a supratentorial CA within or close to eloquent brain areas. RESULTS: A total of 109 patients (66.1% women; mean age 38.4 ± 12.5 yr), were studied. Age >38 yr (odds ratio [OR], 7.33; 95% confidence interval [CI], 1.53-35.19; P  = .013) and time to surgery > 12 mo (OR, 18.21; 95% CI, 1.11-296.55; P  = .042) are independent predictors of uncontrolled seizures at the time of surgery. Focal deficit (OR, 10.25; 95% CI, 3.16-33.28; P  < .001) is an independent predictor of inability to work at the time of surgery. History of epileptic seizures at the time of surgery (OR, 7.61; 95% CI, 1.67-85.42; P  = .003) and partial resection of the CA and/or of the hemosiderin rim (OR, 12.02; 95% CI, 3.01-48.13; P  < .001) are independent predictors of uncontrolled seizures postoperatively. Inability to work at the time of surgery (OR, 19.54; 95% CI, 1.90-425.48; P  = .050), Karnofsky Performance Status ≤ 70 (OR, 51.20; 95% CI, 1.20-2175.37; P  = .039), uncontrolled seizures postoperatively (OR, 105.33; 95% CI, 4.32-2566.27; P  = .004), and worsening of cognitive functions postoperatively (OR, 13.71; 95% CI, 1.06-176.66; P  = .045) are independent predictors of inability to work postoperatively. CONCLUSION: The functional-based resection using intraoperative functional brain mapping allows safe resection of CA and the peripheral hemosiderin rim located within or close to eloquent brain areas.